The Effect of Using Peer on Self-Care, Quality of Life, and Adherence in Elderly People with Coronary Artery Disease - Mojtaba Roshandel; Mahnaz Rakhshan; Majid Najafi Kalyani (The Scientific World Journal)
Introduction. Coronary artery disease is one of the most common diseases and the cause of death among elderly people. Due to the chronic nature of this disease, regular follow-up, lifestyle changes, and adherence to recommendations can reduce the complications and improve the quality of life among elderly individuals. Given the importance of using educational methods that are based on the patient’s age and disease stage, the present study aimed to investigate the effect of using a peer group on self-care, adherence, and quality of life in elderly people. Method. This single-blind clinical trial was conducted on 30 old patients with coronary artery disease aged 60 years in Shiraz from March to June 2021. The patients were selected using simple random sampling and were then randomly assigned to the peer education and control groups (15 participants in each group) via permuted block randomization. The patients in the peer education group received the necessary education about medications, lifestyle, daily activities, self-care, and adherence through three educational clips by educated peer. The patients in the control group received routine education using two clips by the ward nurses. The levels of self-care, adherence, and quality of life were assessed in the intervention and control groups before and one month after the intervention. Data analysis was performed by SPSS 20 software using an independent t-test, paired sample t-test, and chi-square test. P<0.05 was considered statistically significant. Findings. The results showed no statistically significant difference between the two groups with respect to the mean scores of self-care and quality of life before the intervention (P>0.05). Following the educational intervention, however, a statistically significant difference was found between the two groups concerning the mean scores of self-care and adherence (P<0.05). Moreover, the mean differences between the two groups regarding the three variables were statistically significant before and after the intervention (P<0.05). Conclusion. Education based on multimedia clips by peer was effective in increasing the mean scores of self-care, adherence, and quality of life among the elderly people with coronary artery disease. Given the low cost, high effectiveness, and decrease in the nurses’ workload, this method is recommended to be used alongside other methods in order to educate elderly individuals suffering from coronary artery disease.